2008
DOI: 10.1098/rsta.2007.2184
|View full text |Cite
|
Sign up to set email alerts
|

Localization of intense electromagnetic waves in plasmas

Abstract: We present theoretical and numerical studies of the interaction between relativistically intense laser light and a two-temperature plasma consisting of one relativistically hot and one cold component of electrons. Such plasmas are frequently encountered in intense laser-plasma experiments where collisionless heating via Raman instabilities leads to a high-energetic tail in the electron distribution function. The electromagnetic waves (EMWs) are governed by the Maxwell equations, and the plasma is governed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…where J T is the total current density vector in the presence of the high-frequency electric field E T . Equating the zeroth-order terms in (30), one obtains (7) and equating terms at scattered frequency, we get…”
Section: Stimulated Raman Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…where J T is the total current density vector in the presence of the high-frequency electric field E T . Equating the zeroth-order terms in (30), one obtains (7) and equating terms at scattered frequency, we get…”
Section: Stimulated Raman Scatteringmentioning
confidence: 99%
“…Kline et al [29] experimentally investigated SRS using a short pulse diffraction limited laser beam near the instability threshold. Recently, Shukla et al [30] reported the localization of intense laser beam in plasma, and Gupta et.al. [31] reported the effect of localization of EPW on SRS where relativistic nonlinearity is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Shukla & Eliasson (2008) contains a combination of new analytical and numerical results on relativistic electron holes within which intense laser light is trapped. Their computer simulations exhibit fascinating stability and dynamics of the coupled electron hole and electromagnetic wave envelopes.…”
mentioning
confidence: 99%